Fracture clinic redesign reduces the cost of outpatient orthopaedic trauma care. Issue 2 (February 2016) - Jenkins, P. J.; Morton, A.; Anderson, G.; Van Der Meer, R. B.; Rymaszewski, L. A.
Abstract : Objectives: "Virtual fracture clinics" have been reported as a safe and effective alternative to the traditional fracture clinic. Robust protocols are used to identify cases that do not require further review, with the remainder triaged to the most appropriate subspecialist at the optimum time for review. The objective of this study was to perform a "top-down" analysis of the cost effectiveness of this virtual fracture clinic pathway. Methods: National Health Service financial returns relating to our institution were examined for the time period 2009 to 2014 which spanned the service redesign. Results: The total staffing costs rose by 4% over the time period (from £1 744 933 to £1 811 301) compared with a national increase of 16%. The total outpatient department rate of attendance fell by 15% compared with a national fall of 5%. Had our local costs increased in line with the national average, an excess expenditure of £212 705 would have been required for staffing costs. Conclusions: The virtual fracture clinic system was associated with less overall use of staff resources in comparison to national cost data. Adoption of this system nationally may have the potential to achieve significant cost savings. Cite this article: P. J. Jenkins. Fracture clinic redesign reduces the cost of outpatient orthopaedic trauma care. Bone Joint Res 2016;5:33–36. doi: 10.1302/2046-3758.52.2000506